2019
DOI: 10.3390/foods8100515
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Allergenic Potential of the Edible Yellow Mealworm (Tenebrio molitor)

Abstract: The edible yellow mealworm (Tenebrio molitor), contains an extremely diverse panel of soluble proteins, including proteins with structural functions such as muscle proteins, as well as proteins involved in metabolic functions such as enzymes. Most of these proteins display a more or less pronounced allergenic character toward previously sensitized people, especially people allergic to shrimps and other shellfish. A mass spectrometry approach following the separation of a mealworm protein, extracted by sodiumdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 81 publications
1
24
0
Order By: Relevance
“…Nevertheless, our method allowed highlighting those muscle proteins, which in Rabani et al 23 represented only a small proportion of the total, are indeed the most abundant. The protein patterns here determined were more similar to the one described by Yi et al 24 and Barre et al 9 for Yellow mealworm (Tenebrio molitor). Yi and colleagues applied for protein extraction a Filter Aided Sample Preparation (FASP) (involving the use of SDS, Urea and DTT).…”
Section: Resultssupporting
confidence: 86%
“…Nevertheless, our method allowed highlighting those muscle proteins, which in Rabani et al 23 represented only a small proportion of the total, are indeed the most abundant. The protein patterns here determined were more similar to the one described by Yi et al 24 and Barre et al 9 for Yellow mealworm (Tenebrio molitor). Yi and colleagues applied for protein extraction a Filter Aided Sample Preparation (FASP) (involving the use of SDS, Urea and DTT).…”
Section: Resultssupporting
confidence: 86%
“…A total of 20 articles were included in this systematic review -19 obtained through database research and 1 (Jiang et al, 2016) obtained through screening of the references of included studies (although it was published in 2016, it was included since it was not present in our previous review) (Figure 1). Of these 20 articles, 8 studied cross-reactivity or cosensitisation with either crustaceans or HDM (Barre et al, 2019;Beaumont et al, 2019;Broekman et al, 2017a;Hall et al, 2018;Kamemura et al, 2019;Pali-Scholl et al, 2019;Palmer et al, 2020;Sokol et al, 2017), 5 focused on primary sensitisation (Broekman et al, 2017a,b;Francis et al, 2019;Jeong et al, 2017;Nebbia et al, 2019), 1 evaluated allergenic potential of insect tropomyosin (Klueber et al, 2020), 3 studied the effects of food processing techniques on insects' allergenicity (Hall et al, 2018;Hall and Liceaga, 2020;Pali-Scholl et al, 2019), 4 were case reports or case series (Beaumont et al, 2019;Gadisseur et al, 2019;Nebbia et al, 2019;Sokol et al, 2017), 3 assessed the frequency of food allergies or food anaphylaxis caused by insects (Jiang et al, 2016;Lee et al, 2019;Rangkakulnuwat et al, 2020) and 2 assessed the prevalence of allergic reaction among insect-eaters (Chomchai et al, 2020;Taylor and Wang, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Both proteomic and 2D electrophoresis results were consistent with previously published work on the characterization of T. molitor proteins. These studies identified many pan-allergens, such as muscle proteins (actin, myosin, tropomyosin) [ 15 , 32 , 39 ], hemolymph proteins (hexamerin 1 and 2) [ 15 , 32 , 39 ], and proteins associated with various metabolic activities (arginine kinase, α-amylase) [ 39 , 40 , 41 ], to be the most abundant in T. molitor. Overall, the protein profiles were quite similar for the four fractions although specific differences in the abundance of major proteins were observed.…”
Section: Discussionmentioning
confidence: 99%